Analisis Yuridis Penegakan Hukum Terhadap Tindak Pidana Penipuan dengan Modus Lowongan Kerja Melalui Media Sosial Berdasarkan Hukum Positif di Indonesia - Laurentius Chrisendo M.S. (Publikasi Indonesia, 2023)
The impact of globalization is rapid technological progress. Information and the internet make it easier for people to communicate and work. However, technological developments also carry the risk of online crime, especially job fraud through social media. The COVID-19 pandemic increased the number of layoffs and created a need for job vacancies. However, job scams are increasingly rife. Social media is becoming a means of fraud with an increasingly sophisticated mode. The public must be careful in choosing the right information. In the new normal, companies open job openings, but fraud remains a threat to watch out for. This research uses normative and empirical juridical approach methods to examine the implementation of legal rules in society. Data was collected through field studies and analysis of related legal documents. The results of this study state that the mode of job vacancies through social media still often occurs in Indonesia due to law enforcement constraints, limited knowledge, difficulty catching perpetrators, and lack of adequate law enforcement support facilities. Prevention efforts have also not reached an adequate level of effectiveness.